Study on the Influence of Cattle Keeping on the Bacteriological Quality of Domestic Well Water - George T Oommen (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1981)
Wells are the main sources of water supply in Indian villages and towns as elsewhere in any of the rural areas of the developing tropical countries. The shallow, open, dug wells are liable to contamination from the surrounding sources by various means. Faecal contamination of water is considered as one of the major causes of health hazards resulting in innumerable diseases among people throughout the world. Therefore, the bacteriological analysis of water is aimed at the detection and enumeration of indicators of faecal pollution. The movement of animal excreta into surface and ground water is considered a major factor contributing to the bacteriological pollution of available water in many regions.